Settlement characteristics of major infrastructures in Shanghai - X. Jiao; X. Jiao; X. X. Yan; X. X. Yan; H. M. Wang; H. M. Wang (Proceedings of the International Association of Hydrological Sciences, 2015)
Critical infrastructures in Shanghai have undergone uneven settlement since their operation, which plays an important role in affecting the security of Shanghai. This paper, taking rail transportation as example, investigates settlement characteristics and influencing factors of this linear engineering, based on long-term settlement monitoring data. Results show that rail settlement is related to geological conditions, regional ground subsidence, surrounding construction activities and structural differences in the rail systems. In order to effectively decrease the impact of regional ground subsidence, a monitoring and early-warning mechanism for critical infrastructure is established by the administrative department and engineering operators, including monitoring network construction, settlement monitoring, information sharing, settlement warning, and so on.